As-Tsaqafah (Islamic socialization) in planning public spaces – Malaysian experience - Asmawi, M. Zainora; Abdul Malek, Nurhayati; Abdul Aziz, Maimunah (Art University of Isfahan, 2013)
Of late it is noticeable that public spaces have considerably become a significant element in urban fabric as it relates very much with the quality of life of community. A meaningful planning and design of public spaces is crucial as it encourages positive activities for communities to make it more active and lively. Public spaces like parks, pocket gardens, outdoor seating and eating areas, and pedestrian malls are among the trend of this contemporary era among city dwellers globally. Unfortunately, most of the current ideas of planning and designing the public spaces are simply focused to provide spaces for people to do their leisure without respect to Islamic human moral and behavior. Thus, this paper addresses the importance of incorporating the element of as-tsaqafah (Islamic socialization) in planning public spaces. The Islamic perspective is far different from the Western adaptation and modernity style in the social activities. The issues of the right of women, children, family law, security, privacy and gender relationship are seldom being considered and observed in planning public spaces. As such, this paper discusses this issue in the context of Malaysian experiences. Observation on the selected case study was undertaken and analysis indicates that the element of as-tsaqafah is not a priority in planning and design public spaces. It is hoped that this paper could promote some Islamic values and approaches in planning public spaces, taking into consideration the importance of as-tsaqafah values.